Balance of the Labor Policy of the Current Government - Gamarra Vílchez, Leopoldo (2016)
This paper analyzes the employment policy of the current Peruvian government. We begin with some considerations on the economic and social context of the period 2011-2015 and specifically on the concept of precariousness in employment. Then we analyze the most important changes in labor and social security matters; finally, we will discuss some proposals for concrete measures regarding the search for solution of the problems addressed.